Characterizations of Clifford semigroup digraphs - S. Panma (2018)
This paper characterizes directed graphs which are Cayley graphs of strong semilattices of groups and, in particular, strong chains of groups, i.e. of completely regular semigroups which are also called Clifford semigroups. © 2006 Elsevier B.V. All rights reserved.